(untitled) (African Journal of Law and Politics, 2025)
The importance of water to the human society cannot be undermined. Protecting and managing water as a valuable resource of the earth for the use of the present and future generations. For communities, this is crucial especially as living on earth could become so difficult and meaningless when this precious natural resource-water is not properly managed. Potable water has economic, ecological, societal, and cultural functions amongst others. As such, an effective management greatly determines sustainability. The availability of water ensures several tangible and intangible benefits/services to mankind. To this end, there is need to ensure an effective regulation and protection in order to guarantee the continuous supply and enjoyment of the valuable services provided. This study examined the concept of sustainable water management in Cameroon and seeks to understand the reason why access to potable water continues to be a major challenge for many homes in Cameroon, manifested by water scarcity, poor water quality and depletion of potable water sources despite the presence of legal mechanisms providing a benchmark for regulating the sustainability of potable water. To provide an answer to this worry, the study sets to investigate the various mechanisms or techniques employed by the government in ensuring water sustainability as we as the challenges hindering this sector. To realize this objective, data has been collected and analyzed using the typical doctrinal research method. In the end, the paper clamours for legal and institutions reforms as well as a collaborative commitment of State and non-State actors towards ensuring water sustainability.